Spatial and layer-controlled variability in fracture networks. (March 2018) - Procter, Andrew; Sanderson, David J.
Abstract: Topological sampling, based on 1) node counting and 2) circular sampling areas, is used to measure fracture intensity in surface exposures of a layered limestone/shale sequence in north Somerset, UK. This method provides similar levels of precision as more traditional line samples, but is about 10 times quicker and allows characterization of the network topology. Georeferencing of photographs of the sample sites allows later analysis of trace lengths and orientations, and identification of joint set development. ANOVA tests support a complex interaction of within-layer, between-layer and between-location variability in fracture intensity, with the different layers showing anomalous intensity at different locations. This variation is not simply due to bed thickness, nor can it be related to any obvious compositional or textural variation between the limestone beds. These results are used to assess approaches to the spatial mapping of fracture intensity. Graphical abstract: Image 1 Highlights: Node counting in circles allows precise and rapid characterization of fracture networks. Rectified photographs allow later analysis of lengths, orientations, and age. ANOVA shows fracture intensity is controlled by location and layering. Results used to assess approaches to spatial mapping of fracture intensity.